Molecular docking of alkaloid compounds from the pule pandak plant (Rauvolfia serpentina L.) as inhibitors of angiotensin-converting enzyme - Rahma, Annisa Nur; Aghalfi, Revin Rindra Aghalfi; Panggabean, Diva Selviana; Muflihah, Hanny; Gusman, Adisti Faradilla; Aulia, Yasinta Sahma; Regita, Putu Ayu; Auli, Winni Nur; Saputro, Anjar Hermadi (Pharmacy Reports, 2022)
Hypertension is a major global health issue requiring effective treatments with minimal side effects. The angiotensin-converting enzyme (ACE) is a key target in hypertension therapy, and plant-derived compounds are being explored as potential ACE inhibitors. The pule pandak plant (Rauvolfia serpentina L.) contains alkaloid compounds that may have antihypertensive properties. This study aimed to evaluate the potential of alkaloid compounds (ajmaline, rescinnamine, reserpine, and serpentine) from the pule pandak plant as antihypertensive agents using an in silico molecular docking approach. Molecular docking was conducted to analyze the binding affinity of the alkaloid compounds to the ACE protein (PDB ID: 1UZF). Binding free energy values were calculated using AutoDockTools software. The ajmaline-1UZF complex exhibited the lowest binding free energy (-5.89 kcal/mol), indicating the strongest binding affinity among the tested compounds. This suggests that ajmaline has the highest inhibitory potential for ACE.